(untitled) (Research, Society and Development, 2021)
Computational thinking includes skills needed to work with problem solving and, in the educational field, it covers discussions about how it would be possible to improve pedagogical practices related to the inclusion of people with disabilities and high abilities or giftedness. This research reports experiences of the research group "Computing Technologies in teaching and learning from the perspective of Diversity, Inclusion, and Innovation". A survey of existing articles in the Web of Science and Google Academic databases was carried out to discuss proposals related to new ways of thinking about teaching methodologies, involving computational thinking and inclusion. As a result, we propose new approaches that favor inclusive pedagogical practices, we point to the reformulation of the pillars of computational thinking, based on specific teaching needs, suggesting a step-by-step work for all those interested in fostering an education that is effectively more inclusive. We conclude, then, that inclusive computational thinking is applicable in formal or informal education, and is necessary for the holistic development of subjects, facing the demands of the 21st century.